2016
DOI: 10.1016/j.ijporl.2016.06.016
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying predictive factors for long-term complications following button battery impactions: A case series and literature review

Abstract: Based on case reviews, advancements in battery manufacturing, and laboratory research, there are distinct clinical factors that should be assessed at the time of initial therapy to guide follow-up management to minimize potential catastrophic sequelae of button battery ingestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 14 publications
(28 reference statements)
2
42
0
5
Order By: Relevance
“…This finding is in accordance with previous literature [3, 5, 10]. Animal studies have shown that necrosis of the lamina propria in the esophagus can develop within 15 min and can expand to the outer muscular layer of the esophagus within 30 min after button battery ingestion [13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in accordance with previous literature [3, 5, 10]. Animal studies have shown that necrosis of the lamina propria in the esophagus can develop within 15 min and can expand to the outer muscular layer of the esophagus within 30 min after button battery ingestion [13].…”
Section: Discussionsupporting
confidence: 93%
“…Animal studies have shown that necrosis of the lamina propria in the esophagus can develop within 15 min and can expand to the outer muscular layer of the esophagus within 30 min after button battery ingestion [13]. Serious complications after the ingestion of button batteries are described in children both with removal of the battery within a short period after ingestion (2–2.5 h) and with removal after a longer period (3 months) [3, 5, 10]. Even after removal, complications can still develop.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant damage could at times be fatal, depending on the site of lodgement 3. Among the various prognostic factors predicting long-term morbidity due to button battery insertion, ‘the time since impaction’ remains one of the important factor 5. Longer this charged foreign body stays in contact with a mucosal surface, larger is the surrounding tissue necrosis and higher is the probability of long-term morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 BBs impacted in the nasal cavity can cause complications, such as septal perforation, synechia, atrophy, necrosis, and saddle nose. [5][6][7][8][9][10][11][12] BBs also may cause periorbital cellulitis. 13 When the narrower negative poles of the BBs come into contact with the mucosa, they increase the pH by forming hydroxide ions in the tissue due to the electrical discharge.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to tissue injury resulting from alkaline liquefactive necrosis, which is the pathogenesis mechanism responsible for complications. 5 Moreover, it has been suggested that this effect starts in as little as 2 hours. 14,15 In their esophageal models, Jatana et al investigated the basic mechanism of BB ingestion injuries and demonstrated the mitigation of BB-related alkali injuries with the neutralization strategies that they developed and had started to apply clinically to children.…”
Section: Introductionmentioning
confidence: 99%